COGNITIVE IMPAIRMENT, FATIGUE, AND WORKPLACE ACCOMMODATIONS IN MULTIPLE SCLEROSIS: IMPACT ON EMPLOYMENT RETENTION - Cezary Kosmecki; Szymon Zysiak; Dawid Głaz; Łukasz Deska; Magdalena Stolarczyk; Wojciech Sołtys; Natalia Kamińska; Maksymilian Głaz; Jędrzej Zaguła; Aleksandra Jagura-Sukiennik (International Journal of Innovative Technologies in Social Science, 2026)
Multiple Sclerosis significantly impacts employment retention due to its early onset and progressive nature, necessitating a comprehensive understanding of contributing factors beyond physical disability. This narrative review explores the profound influence of cognitive impairment, fatigue, and the efficacy of workplace accommodations on maintaining employment for individuals with MS. Specifically, this review synthesizes current literature to delineate how these non-physical symptoms frequently precipitate job loss and absenteeism among people with MS (pwMS). Beyond merely physical limitations, factors such as fatigue, cognitive decline, and mental health issues are significant predictors of reduced working hours and early retirement for individuals with MS (Pokryszko-Dragan et al., 2022). These non-motor symptoms can create a complex "vicious circle" that adversely affects vocational status, often intertwining with mental health challenges that independently influence professional activities (Pokryszko‐Dragan et al., 2022). The diverse manifestations of MS, encompassing motor, sensory, and cognitive deficits, along with chronic fatigue, significantly impede work performance and overall quality of life (Pokryszko-Dragan et al., 2022; Valadkevičienė et al., 2024). While previous research has identified disease severity, fatigue, and cognitive impairments as key predictors of employment outcomes, persistent limitations in generalizability stem from sample variability, socioeconomic factors, and diverse healthcare systems (Iron et al., 2025). This narrative review aims to comprehensively address these gaps by synthesizing evidence on the multifaceted interplay between cognitive impairment, fatigue, workplace accommodations, and their collective impact on employment retention in MS. Understanding these intricate relationships is critical for developing targeted interventions and supportive strategies to enhance vocational longevity for individuals living with MS (Moccia et al., 2022; Pokryszko‐Dragan et al., 2022).